2020
DOI: 10.3390/biom10030494
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MECP2 and CCR5 Polymorphisms on the Development and Course of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic and systemic autoimmune disease. SLE is described by production of autoantibodies and causes damage of many organs. T-cells play a crucial role in SLE pathogenesis. T-cells intensify inflammation through a number of processes, which leads to autoimmunization. CCR5 and MECP2 genes are linked with T-cells and pathogenesis of SLE. Polymorphisms in these genes are related with the prognostic factors of risk of disease onset and disease severity. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This would suggest the role of biogeographic background in the association of the rs333 variability and the susceptibility to SLE. On the other hand, the lack of association was also reported in patients from Poland [ 43 ], Iran [ 44 ] the Netherlands [ 45 ] and Spain [ 46 ]; the observation being consistent with that made in this study. Conversely, the association was revealed in a mixed cohort of patients from Ohio, Colombia and San Antonio (Texas) [ 26 ] as well as in a female sample from Brazil [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would suggest the role of biogeographic background in the association of the rs333 variability and the susceptibility to SLE. On the other hand, the lack of association was also reported in patients from Poland [ 43 ], Iran [ 44 ] the Netherlands [ 45 ] and Spain [ 46 ]; the observation being consistent with that made in this study. Conversely, the association was revealed in a mixed cohort of patients from Ohio, Colombia and San Antonio (Texas) [ 26 ] as well as in a female sample from Brazil [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Actually, there are conflicting reports as to how the deletion within the CCR5 gene affects the SLE development. While some studies showed its protective effect for disease propensity [ 18 , 24 ], other reports demonstrated no influence [ 43 – 47 ] or even an increased risk of developing SLE [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MECP2 reduces the release of IFN-γ by Th cells, producing a partial immune inhibition [ 30 ]. Previous studies revealed a possible genetic association of MECP2 single-nucleotide polymorphisms (SNPs) with susceptibility to SLE [ 23 , 29 , 31 , 32 , 33 , 34 ]; moreover, MECP2 rs2734647 is related to other diseases, such as Rett syndrome [ 35 ], schizophrenia [ 36 ], and aggressive social behavior [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doudar et al [ 31 ] found that the A allele of MECP2 rs1734791 is the risk allele for lupus in Egyptian populations. Rzeszotarska et al [ 34 ] stated that rs2075596, rs1734787, rs17435, and rs2239464 within the MECP2 gene are more common in SLE patients than in healthy controls and could possibly constitute predictive elements for the progression and course of SLE in Polish populations. Alesaeidi et al [ 39 ] found that in Iranian patients, rs1734787 and rs1734791 of MECP2 were correlated with SLE progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation